2017
DOI: 10.1111/ppl.12568
|View full text |Cite
|
Sign up to set email alerts
|

An update on the regulation of photosynthesis by thylakoid ion channels and transporters in Arabidopsis

Abstract: In natural, variable environments, plants rapidly adjust photosynthesis for optimal balance between light absorption and utilization. There is increasing evidence suggesting that ion fluxes across the chloroplast thylakoid membrane play an important role in this regulation by affecting the proton motive force and consequently photosynthesis and thylakoid membrane ultrastructure. This article presents an update on the thylakoid ion channels and transporters characterized in Arabidopsis thaliana as being involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 64 publications
(141 reference statements)
2
26
0
Order By: Relevance
“…In line with earlier results, vccn1-2 mutants were less capable of inducing qE and thus NPQ in response to increased light intensities (Duan et al, 2016;Spetea et al, 2017). This behavior became apparent on day 3 (sinusoidal fluctuating light conditions) when vccn1-2 displayed significantly decreased NPQ and qE during the high light pulses around midday ( Fig.…”
Section: Dynamic Environmental Photosynthetic Imaging Reveals Distincsupporting
confidence: 90%
“…In line with earlier results, vccn1-2 mutants were less capable of inducing qE and thus NPQ in response to increased light intensities (Duan et al, 2016;Spetea et al, 2017). This behavior became apparent on day 3 (sinusoidal fluctuating light conditions) when vccn1-2 displayed significantly decreased NPQ and qE during the high light pulses around midday ( Fig.…”
Section: Dynamic Environmental Photosynthetic Imaging Reveals Distincsupporting
confidence: 90%
“…Intriguingly, both Lhcb1 and Lhcb2 proteins contain several additional phosphosites that do not seem to be phosphorylated by STN7 or STN8, 121 leaving their function to be solved. In addition to phosphorylation, ion fluxes are also known to be involved in the regulation of thylakoid ultrastructure 122 but their interaction with phosphorylation of Lhcb proteins is likewise still elusive. Further, recent research has shown that thylakoid protein acetylation is also required for the regulation of excitation energy balancing between the two photosystems, 123 introducing a whole new aspect of post-translational protein modification for regulation of photosynthesis.…”
Section: Reversible Lhcii Antenna Phosphorylationmentioning
confidence: 99%
“…Another known role of thylakoid Cl − is in parsing the PMF across the thylakoid membrane into an inside‐positive electrical potential difference and inside‐low pH difference (van Kooten et al , 1986; Cruz et al , 2001; Tang & Wei, 2001; Herdean et al , 2016a,b; Davis et al , 2017; Spetea et al , 2017; Szabò & Spetea, 2017). Light‐driven pumping of H + into the thylakoid lumen immediately results in an electrical potential difference across the membrane.…”
Section: Other Photosynthetic Roles Of Cl−mentioning
confidence: 99%